2016
DOI: 10.1038/srep31945
|View full text |Cite
|
Sign up to set email alerts
|

Association of Adiponectin Polymorphism with Metabolic Syndrome Risk and Adiponectin Level with Stroke Risk: A Meta-Analysis

Abstract: Many previous studies have provided evidence that the ADIPOQ +45T>G polymorphism (rs2241766) might cause metabolic syndrome (MS). As a cardiovascular manifestation of MS, the incidence of stroke is associated with adiponectin; however, the results remain controversial and inconsistent. Systematic searches of relevant studies published up to Dec 2014 and Jan 2016 on the ADIPOQ +45T>G polymorphism and the risk of MS and adiponectin levels and the risk of stroke, respectively, were conducted in MEDLINE and EMBASE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…Lastly, the cross-sectional study could not confirm any causal relationship. One study suggested that adiponectin level was not a causal factor of increasing stroke risk [65].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, the cross-sectional study could not confirm any causal relationship. One study suggested that adiponectin level was not a causal factor of increasing stroke risk [65].…”
Section: Discussionmentioning
confidence: 99%
“…Prior studies found that modulation of ADPQ level and the susceptibility of insulin resistance might share a common genetic basis located in the human 3q27 locus (Vasseur et al, 2003 ; Yang and Chuang, 2006 ). Accordingly, key variations of the APM1 gene that encodes ADPQ protein were associated with MetS prevalence (Gao et al, 2013 ; Yuan et al, 2016 ). However, the causative role of ADPQ levels as an overall phenotype based on a gene-environmental interaction upon MetS occurrence has not been systematically reviewed to date.…”
Section: Discussionmentioning
confidence: 99%
“…The quality of the identified studies was assessed according to a “methodological quality assessment scale,” which was modified from the study by Yuan et al (2016). Five items, including the representativeness of the cases, the source of controls, sample size, quality control of the genotyping methods, and HWE, were evaluated on this scale.…”
Section: Methodsmentioning
confidence: 99%